Analisis Kepuasan Pasien Terhadap Pelayanan Klinik Maesa Dental Menggunakan Metode Weighted Product (WP) - Naula Shalfa Nabila; Nilam Mukaromah; Angga Cakraswara (CV. Shofanah Media Berkah, 2025)
Patient satisfaction is one of the main indicators in assessing the quality of health services, especially in dental clinic services. Maesa Dental Clinic, which has been established for more than 10 years and has several branches, namely Pamulang, Gading Serpong, Senopati, and Karawaci, needs to conduct regular evaluations to ensure the quality of its services is maintained. This study aims to analyze the level of patient satisfaction with Maesa Dental Clinic services using the Weighted Product (WP) method. The research data was obtained from the results of questionnaires filled out by patients over a period of one month using a Likert scale of 1–5. The criteria used include How is the overall cleanliness and tidiness of the clinic, How is the cleanliness and availability of facilities in the toilet, How is the friendliness and professionalism of the reception staff, How is the quality of service from the dentist who treated you, How is the quality of service from the dentist who treated you. The Weighted Product method is used to process data based on the weight of each criterion to obtain a preference value for the level of patient satisfaction. The results show that the level of patient satisfaction with Maesa Dental Clinic services is in the very satisfied category. The quality of medical personnel services and staff friendliness are the most influential factors on patient satisfaction. Thus, it can be concluded that Maesa Dental Clinic has been able to provide quality services that meet patient expectations. The results of this study are expected to serve as evaluation material and a reference for clinic management in efforts to improve service quality in the future.